Penerapan Aplikasi iDINI sebagai Media Penyimpanan Materi Perkuliahan iLearning Pada Perguruan Tinggi - Untung Rahardja; Ary Budi Warsito; Dini Nurul Suvianti (Universitas Raharja, 2012)
Era of globalization is happening now require human resources to complete, on the other side of Indonesia's human resources do not meet the above criteria. Even qualitatively, the fact shows that Indonesia's human resources is quite low and tends to decrease. Low indicators of human resources of Indonesia can be seen in student achievement. The problem is still quite low level of education of Indonesia's human resources is a challenge for the state of education in Indonesia. Indonesia needs to improve the quality of education for human resource produced as expected, decreased detection performance learn should start from the educator as the spearhead of educational success .. This method can optimize the potential of intellectual, social and emotional development of students. This is one thing why the medium of learning is necessary in the learning process. Medium of learning is one component of learning that has an important role in the learning process. Use of media should be a part that should receive the attention of teachers as facilitators of learning in every activity. Because of its individual thateducators need to learn how to establish a medium of learning in order to effectively achieve the goal of learning in the learning process. In fact the learning media is still often overlooked by many reasons.